Colorful Luminescent Magnetic Supraparticles: Expanding the Applicability, Information Capacity, and Security of Micrometer‐Scaled Identification Taggants by Dual‐Spectral Encoding. Issue 13 (10th February 2022) - Müssig, Stephan; Reichstein, Jakob; Miller, Franziska; Mandel, Karl
Abstract: (Sub)micrometer‐scaled identification (ID) taggants enable direct identification of arbitrary goods, thereby opening up application fields based on the possibility of tracking, tracing, and anti‐counterfeiting. Due to their small dimensions, these taggants can equip in principle even the smallest subcomponents or raw materials with information. To achieve the demanded applicability, the mostly used optically encoded ID taggants must be further improved. Here, micrometer‐scaled supraparticles with spectrally encoded luminescent and magnetically encoded signal characteristics are reported. They are produced in a readily customizable bottom‐up fabrication procedure that enables precise adjustment of luminescent and magnetic properties on multiple hierarchy levels. The incorporation of commonly used magnetic nanoparticles and fluorescent dyes, respectively, into polymer nanocomposite particles, establishes a convenient toolbox of magnetic and luminescent building blocks. The subsequent assembly of selected building blocks in the desired ratios into supraparticles grants for all the flexibility to freely adjust both signal characteristics. The obtained spectrally resolved visible luminescent and invisible magnetic ID signatures are complementary in nature, thus expanding applicability and information security compared to recently reported optical‐ or magnetic‐encoded taggants. Additionally, the introduced ID taggant supraparticles can significantly enhance the coding capacity. Therefore, the introduced supraparticles are considered as next‐generation ID taggants. Abstract : (Sub)micrometer‐scaled identification taggants enable direct identification of arbitrary goods, thereby opening up application fields based on the possibility of tracking, tracing, and anti‐counterfeiting. Herein, dual‐spectrally encoded luminescent and magnetic micrometer‐scaled supraparticles with a huge code variety are presented. The complementary visible and invisible signal characteristics expand applicability and information security compared to solely optical‐ or magnetic‐encoded taggants.